Body image as a global mental health concern - Rachel F. Rodgers; Katherine Laveway; Priscila Campos; Pedro Henrique Berbert de Carvalho (Cambridge Prisms: Global Mental Health, 2023)
Body image concerns related to weight or other dimensions of appearance are now prevalent on a global scale. This paper reviews the theoretical frameworks that account for the global similarities and regional differences in rates and presentation of body image concerns, as well as reviewing the extant data. Given the harmful consequences of body image concerns in terms of mental and physical health, their global burden is high. Interventions to mitigate these concerns at the individual and systemic level are warranted.